PENGARUH STRATEGI PROSES BELAJAR MENGAJAR TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA (STUDI PADA SMP SWASTA RIAMA MEDAN) - Zulmawati Zulmawati (Universitas Negeri Medan, 2019)
This study aims to look at the effect of the teaching and learning process strategy on improving PKn student achievement at the Riama Private Middle School in Medan. The method used in this study is descriptive analysis with a population of 30 students and 3 Civics teachers. As for the variables in this study were independent variables (x) namely the teaching learning process planning and the dependent variable (y) namely achievement student learning. Techniques and tools for data collection are by conducting observations (observation and review), questionnaires (list of written questions) to obtain information from respondents who contain questions by completing answers to choose one of the answers that are already available as where the actual situation is After all answers are collected, the data are grouped to analyze each question item in accordance with the provisions. The data processing is divided into two parts, namely data from the teacher and data from the private junior high school students in the field. The results achieved according to the method used in this study are accepted. And so that the teachers can arrange teaching plans in the learning process better. Keywords: Strategy, Teaching and Learning Process, Learning Achievement.